Synthesis of 2D Metal Chalcogenide Thin Films through the Process Involving Solution‐Phase Deposition. Issue 25 (24th April 2018) - Giri, Anupam; Park, Gyeongbae; Yang, Heeseung; Pal, Monalisa; Kwak, Junghyeok; Jeong, Unyong
Abstract: 2D metal chalcogenide thin films have recently attracted considerable attention owing to their unique physicochemical properties and great potential in a variety of applications. Synthesis of large‐area 2D metal chalcogenide thin films in controllable ways remains a key challenge in this research field. Recently, the solution‐based synthesis of 2D metal chalcogenide thin films has emerged as an alternative approach to vacuum‐based synthesis because it is relatively simple and easy to scale up for high‐throughput production. In addition, solution‐based thin films open new opportunities that cannot be achieved from vacuum‐based thin films. Here, a comprehensive summary regarding the basic structures and properties of different types of 2D metal chalcogenides, the mechanistic details of the chemical reactions in the synthesis of the metal chalcogenide thin films, recent successes in the synthesis by different reaction approaches, and the applications and potential uses is provided. In the last perspective section, the technical challenges to be overcome and the future research directions in the solution‐based synthesis of 2D metal chalcogenides are discussed. Abstract : The recent progress regarding the synthesis and applications of solution‐based two‐dimensional metal chalcogenide thin films is reviewed, and a perspective thereon is presented. The mechanistic details of the chemical transformation process during thin‐film synthesis, recent successes in synthesis by different reaction approaches, and applications are summarized. Finally, technical challenges in the solution‐based approach and future research directions are discussed.